Assessing the Online Teaching Readiness Competencies Among the College Faculty of Adventist Medical Center - Junge B. Guillena (International Journal Labs, 2022)
This study aimed to determine the readiness competencies for online teaching and the confidence to teach online among the college faculty in Adventist Medical Center College (AMCC) Iligan for the Academic Year 2020-2021. This study utilized a cross-sectional research design with forty-one (41) sampled Adventist Medical Center College (AMCC) voluntarily participating. Results indicated that the faculty rated very important and more confident in creating quizzes and tests and online assignments but noticeably scored low in creating instructional videos and managing grades online. Demographic profiles like age, gender, the department assigned, and years of teaching experience have no significant effect on the level of importance of online teaching competencies and their confidence to teach online. Thus, the result signified that the perceived assessment of the faculty on the importance of the online teaching competencies and their ability to conduct online were comparable across their characteristics.